2014
DOI: 10.1155/2014/276457
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of MMP-14 and TIMP-3 Expression with Macrophage Activation and Human Atherosclerotic Plaque Vulnerability

Abstract: Matrix metalloproteinase-14 (MMP-14) promotes vulnerable plaque morphology in mice, whereas tissue inhibitor of metalloproteinases-3 (TIMP-3) overexpression is protective. MMP-14hi  TIMP-3lo rabbit foam cells are more invasive and more prone to apoptosis than MMP-14lo  TIMP-3hi cells. We investigated the implications of these findings for human atherosclerosis. In vitro generated macrophages and foam-cell macrophages, together with atherosclerotic plaques characterised as unstable or stable, were examined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 41 publications
4
50
1
3
Order By: Relevance
“…MMPs are a class of proteases involved in extracellular matrix degradation, which appear to play a key role in the process of vascular remodeling during the course of vascular disease [34,35] . Numerous studies suggest that MMPs and in particular MMP-3, MMP-7, MMP-9 and MMP-12, may be involved in the process of plaque destabilization [36,37] . However there are conflicting results in particular regarding MMP-3.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are a class of proteases involved in extracellular matrix degradation, which appear to play a key role in the process of vascular remodeling during the course of vascular disease [34,35] . Numerous studies suggest that MMPs and in particular MMP-3, MMP-7, MMP-9 and MMP-12, may be involved in the process of plaque destabilization [36,37] . However there are conflicting results in particular regarding MMP-3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that MMP-14 is associated with tuberculosis by regulating monocyte migration and collagen destruction (32), and with macrophage activation in atherosclerosis (33). TGF-β1 function has been observed in brain and nerve damage (34).…”
Section: Genementioning
confidence: 98%
“…В результате инфильтрации покрышки атеросклеротической бляшки макрофа-гами и Т-лимфоцитами увеличивается продукция в ней воспалительных цитокинов, ингибирующих пролиферацию ГМК и синтез ими коллагена, а также индуцирующих апоптоз ГМК и протеоли-тическую активность макрофагов. В результате макрофаги и ГМК начинают секретировать проте-олитические MMP, разрушающие коллагены и эла-стин покрышки бляшки, что приводит к ее истон-чению/иссечению, изъязвлению, тромбозу и соот-ветствующим клиническим проявлениям острого коронарного синдрома [11,15].…”
Section: результатыunclassified
“…Высокий уровень экс-прессии белка ММР-14 наблюдался в гладкомышеч-ных клетках и пенистых клетках атеросклеротиче-ской бляшки [2,11].…”
unclassified